If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-3 + 6K) = 0 (-3 * 7 + 6K * 7) = 0 (-21 + 42K) = 0 Solving -21 + 42K = 0 Solving for variable 'K'. Move all terms containing K to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 42K = 0 + 21 Combine like terms: -21 + 21 = 0 0 + 42K = 0 + 21 42K = 0 + 21 Combine like terms: 0 + 21 = 21 42K = 21 Divide each side by '42'. K = 0.5 Simplifying K = 0.5
| 6+(-n)-7=-2 | | 3c-5c=9+4c | | 4x+5=1x+2 | | x/8-(-2)=-3 | | 61.2=6(m+3.6) | | 4w-6=3(w+1) | | 12x+2x=10x+20 | | (3x-2)-x=10 | | 6(y-1/3)=-1.2(2y-10) | | 12y-21/4= | | -x+6y=16 | | 20cosX=-31.3229 | | 8d+4=2d | | 2x+41=83 | | 5x^3+36x+7=0 | | -12y-6x=3 | | x(14x+31)+15=0 | | -7a-2b+7+2b+5a= | | 39,41=120,84 | | (8x-3)-(7x-4)+(-5x+6)= | | 4x^3+12x^2-72x-160=0 | | 7x-28y=35 | | 7x(6x+1)=511 | | 9x+63=8x+59 | | log(9x^2)-log(x)=2 | | 7x+8=3x-24 | | 11x-2=-24 | | combine(8x-3)-(7x-4)+(-5x+6)= | | 3y-2y=1 | | 18=0.9(x-1) | | x+2x+4=21 | | -2/3s-1=56 |